Replacing soybean meal with dried distillers grains and corn gluten feed in meat goats - Griffin, Ashley R.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2019)
In recent years, there has been a higher demand for goat products, specifically goat meat, in the U.S. This has caused the number of goats to nearly double in the past few decades. However, there is very little information on which diets are most economical to grow goats with. In this study, we tested if corn gluten feed (CGF) diet could be a more economically effective way to grow goats than soybean meal (SBM) and dried distillers grains soluble (DDGS). 75 meat Boer-type goats, (26.9±0.2 kg and approximately 70 days of age) were randomly assigned to treatments, with 15 goats per treatment, 3 goats per pen, and the pen as the experimental unit. The 5 treatments were: 1) 100% soybean mean, 2) 100% DDGS, 3) 66.7% DDGS/33.3% CGF, 4) 33.3% DDGS/66.7% CGF, and 5) 100% CGF. All of the diets were isocaloric and isonitrogenous. Throughout the course of the 35 d study, we measured BW, ADG, ADFI, and G:F ratio. We detected no linear effect between these measured values for the different treatments for a linear trend (P>0.05); however, there was a trend for the ADG to decrease when levels of CGF increased (P=0.723). Economics were then evaluated, and we calculated the cost per kilogram of feed, the cost of feeding one goat, and the cost for one kilogram of gain. Diets including CGF reduced the cost of one kg of feed by $0.04. With this lower cost of feed, goats with CGF diets cost less to feed than goats on SBM (P=0.008). However, there were no other detected differences in feed cost, whether for kg of feed or for kg of gain. We concluded that that diets with corn co-products can be an economically efficient replacement for SBM diets in growing goats.
Keywords: Spring 2019